The second ACTRIS inter-comparison (2016) for Aerosol Chemical Speciation Monitors (ACSM): Calibration protocols and instrument performance evaluations. Issue 7 (3rd July 2019) - Freney, Evelyn; Zhang, Yunjiang; Croteau, Philip; Amodeo, Tanguy; Williams, Leah; Truong, François; Petit, Jean-Eudes; Sciare, Jean; Sarda-Esteve, Roland; Bonnaire, Nicolas; Arumae, Tarvo; Aurela, Minna; et al.
Abstract: This work describes results obtained from the 2016 Aerosol Chemical Speciation Monitor (ACSM) intercomparison exercise performed at the Aerosol Chemical Monitor Calibration Center (ACMCC, France). Fifteen quadrupole ACSMs (Q_ACSM) from the European Research Infrastructure for the observation of Aerosols, Clouds and Trace gases (ACTRIS) network were calibrated using a new procedure that acquires calibration data under the same operating conditions as those used during sampling and hence gets information representative of instrument performance. The new calibration procedure notably resulted in a decrease in the spread of the measured sulfate mass concentrations, improving the reproducibility of inorganic species measurements between ACSMs as well as the consistency with co-located independent instruments. Tested calibration procedures also allowed for the investigation of artifacts in individual instruments, such as the overestimation of m / z 44 from organic aerosol. This effect was quantified by the m / z (mass-to-charge) 44 to nitrate ratio measured during ammonium nitrate calibrations, with values ranging from 0.03 to 0.26, showing that it can be significant for some instruments. The fragmentation table correction previously proposed to account for this artifact was applied to the measurements acquired during this study. For some instruments (those with high artifacts), this fragmentation table adjustment led to an "overcorrection" of the f44 ( m / z 44/Org) signal. This correction based on measurements made with pure NH4 NO3, assumes that the magnitude of the artifact is independent of chemical composition. Using data acquired at different NH4 NO3 mixing ratios (from solutions of NH4 NO3 and (NH4 )2 SO4 ) we observe that the magnitude of the artifact varies as a function of composition. Here we applied an updated correction, dependent on the ambient NO3 mass fraction, which resulted in an improved agreement in organic signal among instruments. This work illustrates the benefits of integrating new calibration procedures and artifact corrections, but also highlights the benefits of these intercomparison exercises to continue to improve our knowledge of how these instruments operate, and assist us in interpreting atmospheric chemistry.